Minimally invasive versus conventional sternotomy for Mitral valve repair: protocol for a multicentre randomised controlled trial (UK Mini Mitral). Issue 4 (14th April 2021) - Maier, Rebecca H; Kasim, Adetayo S; Zacharias, Joseph; Vale, Luke; Graham, Richard; Walker, Antony; Laskawski, Grzegorz; Deshpande, Ranjit; Goodwin, Andrew; Kendall, Simon; Murphy, Gavin J; Zamvar, Vipin; et al.
Abstract : Introduction: Numbers of patients undergoing mitral valve repair (MVr) surgery for severe mitral regurgitation have grown and will continue to rise. MVr is routinely performed via median sternotomy; however, there is a move towards less invasive surgical approaches. There is debate within the clinical and National Health Service (NHS) commissioning community about widespread adoption of minimally invasive MVr surgery in the absence of robust research evidence; implementation requires investment in staff and infrastructure. The UK Mini Mitral trial will provide definitive evidence comparing patient, NHS and clinical outcomes in adult patients undergoing MVr surgery. It will establish the best surgical approach for MVr, setting a standard against which emerging percutaneous techniques can be measured. Findings will inform optimisation of cost-effective practice. Methods and analysis: UK Mini Mitral is a multicentre, expertise based randomised controlled trial of minimally invasive thoracoscopically guided right minithoracotomy versus conventional sternotomy for MVr. The trial is taking place in NHS cardiothoracic centres in the UK with established minimally invasive mitral valve surgery programmes. In each centre, consenting and eligible patients are randomised to receive surgery performed by consultant surgeons who meet protocol-defined surgical expertise criteria. Patients are followed for 1 year, and consent to longer term follow-up. Primary outcome is physical functioning 12 weeks following surgery, measured by change in Short Form Health Survey (SF-36v2) physical functioning scale. Early and 1 year echo data will be reported by a core laboratory. Estimates of key clinical and health economic outcomes will be reported up to 5 years. The primary economic outcome is cost effectiveness, measured as incremental cost per quality-adjusted life year gained over 52 weeks following index surgery. Ethics and dissemination: A favourable opinion was given by Wales REC 6 (16/WA/0156). Trial findings will be disseminated to patients, clinicians, commissioning groups and through peer reviewed publication. Trial registration number: ISRCTN13930454 .